Implementation of “Market Day Every Friday" in instilling the values of entrepreneurship education from an early age - Hairul Huda; Siti Khayisatuzahro Nur; Moh Ubaidillah Al Amin (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
The cultivation of entrepreneurial character values is a part of the educational process launched by the Indonesian government. Entrepreneurship education aims to increase added value for students in forming entrepreneurial character. One of the concrete steps to instill entrepreneurial character values in the educational environment is by creating a Market Day activity program. Like the Market Day Every Friday program that has been implemented at SD 1 Muhammadiyah Banyuwangi. This activity is packaged in the form of fun trading activities once a week. This study aims to find out the role of the "Market Day Every Friday" program at SD 1 Muhammadiyah Banyuwangi as an effort to instill entrepreneurial character values in students. This study uses quantitative research methods to determine the role of Market Day Every Friday on the values of entrepreneurship education. The analytical method uses simple regression analysis in the Statistical for the Social Science (SPSS) program. The results of this study state that the market day every Friday program has implications for the values of Entrepreneurship Education for Muhammadiyah 1 Bayuwangi Elementary School students as evidenced by showing that entrepreneurial values are an important point in building entrepreneurial character in the range of 64.5%. This is intended for some students to be able to improve entrepreneurial abilities in various indicators. Then on the market day variable with a value of 47.4%, it shows that the market day program gets recommendations from student parents